Evaluation of Islamic Education: Test Forms and Characteristics - Muhamad Julfa Kamal; Mukh Nursikin (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2026)
This study examines various methods and approaches to learning outcome assessment applied to measure the achievement of learning objectives. The learning outcome evaluation process plays a critical role in detecting the level of competency mastery achieved by students. Various assessment formats, such as written tests (both objective and descriptive), oral exams, attitude observations, student work collections (portfolios), project assignments, and presentations, are used comprehensively to assess students' knowledge, skills, and attitudes. Methodologically, evaluation techniques can be classified into two main approaches: quantitative and qualitative, each with its own advantages and limitations. The development of innovative assessment systems, including the use of technology through online exams and digital portfolios, has significantly increased the efficiency and accuracy of the evaluation process. This study aims to map the variety of evaluation forms and techniques while emphasizing the urgency of selecting contextual methods that consider learning objectives and the unique characteristics of each student.